2010
DOI: 10.1177/0363546510370280
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Activity Level 2 Years after Anterior Cruciate Ligament Reconstruction (ACLR)

Abstract: Objective ACL deficient subjects are at risk of knee injury with cutting and pivoting activities; in accord, ACL reconstructions (ACLR) are performed to restore stability to allow for return to cutting and pivoting activities. The Marx activity level is a validated patient-reported measure to quantify the amount and frequency of running, cutting, decelerating, and pivoting performed. Our objective was to quantify activity level 2 yrs after ACLR and identify explanatory variables measured at baseline (demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
145
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 194 publications
(157 citation statements)
references
References 32 publications
11
145
1
Order By: Relevance
“…Despite many reports of successful outcomes following ACL reconstruction, recent reports have suggested that the rates of return to sport may not match the success of this surgery as measured by other factors [2,4,5,10,13,19,25,31,44]. This discrepancy raises many issues and the purpose of this article is to explore return to sport following ACL reconstruction from a number of perspectives.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Despite many reports of successful outcomes following ACL reconstruction, recent reports have suggested that the rates of return to sport may not match the success of this surgery as measured by other factors [2,4,5,10,13,19,25,31,44]. This discrepancy raises many issues and the purpose of this article is to explore return to sport following ACL reconstruction from a number of perspectives.…”
Section: Discussionmentioning
confidence: 95%
“…Dunn et al tried to quantify some of these factors [13]. They found that a higher pre-injury activity level was the strongest predictor of return to sport at two years after ACL reconstruction, while female gender, a higher body mass index (BMI) and smoking in the first six months prior to surgery were associated with a lower rate of return to sport.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, patients have been studied preoperatively and several months after surgery to determine the effects of ACLR. 2,4,6,12,21,24,25,39,40 This leads one to question the influence that early postoperative stages of recovery have on self-reported outcomes. Our results showed significant associations between patients' subjective IKDC scores during the first 2 months postoperatively and the !12-month IKDC score.…”
Section: Discussionmentioning
confidence: 99%
“…11 Though controversy lingers, substantial research has been conducted on specific surgical procedures, various graft options, and rehabilitation protocols in an attempt to identify prognostic risk factors and modifiable predictors to improve self-reported outcomes after ACLR. 12,13 Although multiple authors have evaluated various factors related to returning individuals to their prior level of function, research identifying the effectiveness of early postoperative measures on self-reported outcomes after ACLR is lacking. Several self-efficacy studies have provided compelling evidence that a large number of patients are unable to return to their prior level of function in spite of an apparently successful surgery and rehabilitation.…”
mentioning
confidence: 99%
See 1 more Smart Citation